Dėmesys sakytinei tradicijai kaip kūrybiškas tapatinimasis. Antano Juškos ir Jono Basanavičiaus etnografinės veiklos motyvų apmąstymas - Jonutytė, Jurga (Literatūra, 2015)
The article focuses on how the attention to an oral tradition is related to the formation of the national identity. Many educated men in the 19th century Lithuania started to collect various elements of oral tradition. In spite of similar cultural situation all over Europe, the situation in Lithuania was quite unusual because of two reasons. Firstly, this meant to focus one’s attention to (or even to identify oneself with) the lowest class of society. The second reason was that the oral tradition was fully alive and rich in that time, it wasn’t transformed to stable symbols, and the value of it wasn’t clear. The focus to this kind of ordinary life details was socially and aesthetically new. The main characters of the article are two important historic actors of the end of XIX century and the beginning of XX century – Antanas Juška and Jonas Basanavičius. They (among the others) where creating new patterns for identification with social level, with professional group, with Lithuanian language speakers and, finally, with nation. The article makes presupposition that the passive identity is of the same relevance in these processes as an active identity (the division between passive and active identities is made according G. Devereux). Basanavičius and Juška had the interest in all details of all branches of the daily life. Their interest was essentially different from the scientific interest in Lithuanian language showed usually by German linguists since the XVIII century. The article makes a hypothesis that the passive identity, which did not receive scholarly attention, can be thematized and fixed in the conscious acts of noticing of oral tradition, and in the acts of recording and declaring it. For the oral tradition, it is transmitting of way how to make, or how to behave, or how to relate to something, rather than transmitting of concrete data to remember that in the verbal form. This is why the focus on the oral tradition could be called an attention to the passive identity as to the specific national way of creating senses of everyday life.